Penilaian Konsumen Dan Strategi Pemasaran Terhadap Produk Tomat Organik (Lycopersicum esculentum Mill) di Kebun Fakultas Pertanian Universitas Nusa Nipa Indonesia - Ignasius R. Budiyanto; Gabriel Otan Apelabi; Yoseph Yakob Da Rato (Jurnal Ilmiah Wahana Pendidikan, 2021)
The background of this research explains that consumer demand and marketing strategies are one of the factors that determine the product level and marketing strategy in a product that is marketed with various aspects that are carried out, namely Product, Price, Place, and Promotion as well as, Marketing Strategy for tomato products. organic. Research on Consumer Assessment and Marketing Strategies of Organic Tomato Products. at the Garden of the Faculty of Agriculture, University of Nusa Nipa, which was held on September 2 to December 4, 2020. This study aims: 1. To measure consumers of organic tomato products and 2. To see the marketing strategy of organic tomato products in the gardens of the Faculty of Agriculture, University of Nusa Nipa, which is in Alok District, Sikka Regency. Sampling in this study used qualitative methods that were not obtained through statistical systems or statistical methods. The research data took the entire population who had bought organic tomato products as many as 50 respondents in the Garden of the Faculty of Agriculture, University of Nusa Nipa and data collection was carried out by survey methods. The data obtained in the form of primary data from direct interviews with respondents based on questions in the questionnaire provided, while the data obtained from related agencies and sources relevant to this study. From the results of the data analysis taken as follows: (1) Most of the respondents admitted that they like and want to repurchase organic tomato products. (2) The strategies that must be taken to increase the marketing of organic tomatoes are in terms of product, price, place and promotion. So that the marketing strategy can be replaced with products, prices, places and promotions that are attractive and easy to get for consumers to buy products marketed by the Garden of the Faculty of Agriculture, University of Nusa Nipa.